2014
DOI: 10.1371/journal.pone.0098155
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Agonist and Antagonist Regulation of Autophagy in HepG2 Cells, Primary Mouse Hepatocytes, and Mouse Liver

Abstract: Autophagy recently has been shown to be involved in normal hepatic function and in pathological conditions such as non-alcoholic fatty liver disease. Adrenergic signalling also is an important regulator of hepatic metabolism and function. However, currently little is known about the potential role of adrenergic signaling on hepatic autophagy, and whether the β-adrenergic receptor itself may be a key regulator of autophagy. To address these issues, we investigated the actions of the β2-adrenergic receptor agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Several lines of evidence link cAMP elevation to induction of autophagy in hepatocytes. First, Farah et al (45) demonstrated that ␤-AR agonists induce LC3-II formation and p62 degradation in primary mouse hepatocytes and human hepatoma cells. Another study showed that caffeine, an adenosine receptor antagonist and phosphodiesterase inhibitor, stimulates lipid metabolism and autophagy (LC3-II increase and p62 decrease), as well as suppresses mTORC1 activity (46).…”
Section: The Camp Pathway: a Central Regulator Of Energy Homeostasismentioning
confidence: 99%
“…Several lines of evidence link cAMP elevation to induction of autophagy in hepatocytes. First, Farah et al (45) demonstrated that ␤-AR agonists induce LC3-II formation and p62 degradation in primary mouse hepatocytes and human hepatoma cells. Another study showed that caffeine, an adenosine receptor antagonist and phosphodiesterase inhibitor, stimulates lipid metabolism and autophagy (LC3-II increase and p62 decrease), as well as suppresses mTORC1 activity (46).…”
Section: The Camp Pathway: a Central Regulator Of Energy Homeostasismentioning
confidence: 99%
“…For T 3 treatments, all cells were grown for at least 3 days in DMEM containing 10% Dowex-stripped FBS and 1ϫ penicillin/streptomycin (normal T 3 -depleted DMEM) before adding T 3 (100 nM; unless mentioned otherwise) with or without other compounds (LY292004, 5 M) at indicated durations in the respective figures. Primary mouse hepatocytes were isolated from male C57BL/6 mice (8 -10 weeks old) using standard twostep collagenase perfusion method, as mentioned previously (26), and cultured in normal T 3 -depleted DMEM as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of lipin‐1 expression has been shown to reduce DAG levels and impair autophagic flux by preventing the normal maturation of autolysosomes during the process of autophagy . Recent studies have confirmed that propranolol blocks the late stages of autophagy, mimicking responses in cells lacking lipin‐1 expression . Lipin‐1 also operates as a transcriptional coactivator, where it is involved in the regulation of lipid metabolism.…”
Section: Targeting Cancer Metabolismmentioning
confidence: 99%
“…231 Recent studies have confirmed that propranolol blocks the late stages of autophagy, mimicking responses in cells lacking lipin-1 expression. 232,233 Lipin-1 also operates as a transcriptional coactivator, where it is involved in the regulation of lipid metabolism.…”
Section: Propranolol As a Modifier Of Sarcoma Cell Metabolismmentioning
confidence: 99%